Natural and magnetic circular dichroism spectra of nucleosides: effect of the dynamics and environment. Issue 14 (23rd February 2021) - Kaminský, Jakub; Andrushchenko, Valery; Bouř, Petr
Abstract : Electronic absorption, natural and magnetic circular dichroism spectra of several nucleosides are simulated to understand their dependence on molecular dynamics and environment, their sensitivity to nucleoside pairing and stacking in nucleic acids. Abstract : Chiroptical spectroscopic methods are excellent tools to study structure and interactions of biomolecules. However, their sensitivity to different structural aspects varies. To understand the dependence of absorption, electronic and magnetic circular dichroism (ECD, MCD) intensities on the structure, dynamics and environment, we measured and simulated spectra of nucleosides and other nucleic acid model components. The conformation space was explored by molecular dynamics (MD), the electronic spectra were generated using time dependent density functional theory (TDDFT). The sum over state (SOS) method was employed for MCD. The results show that accounting for the dynamics is crucial for reproduction of the experiment. While unpolarized absorption spectroscopy is relatively indifferent, ECD reflects the conformation and geometry dispersion more. MCD spectra provide variable response dependent on the wavelength and structural change. In general, MCD samples the structure more locally than ECD. Simple computational tests suggest that the optical spectroscopies coupled with the computational tools provide useful information about nucleic acid components, including base pairing and stacking.